Application of CaTiO3:Pr3+ Phosphor for Enhancing the Hue Standard of WLEDs with Double-Film Distant Phosphor Structure - Dieu An Nguyen Thi; Phan Xuan Le (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2022)
Due to its great thermal stability, the WLEDs (short for white-light diodes), which are made of PiG (short for phosphor-in-glass), appear to be an optical source most effective at generating potent white illumination. However, the actual applications they offer are limited by their poor color rendering and color uniformity. To improve the color rendering and uniformity, this study suggested utilizing a configuration involving a PiG-RPL (short for PiG integrated with a lens of phosphor in red). The phosphor YAGG (also known as Y3Al3.08Ga1.92O12:Ce3+) and borosilicate glass powders were printed, then sintered to generate the green PiG, and then using an inverted dispensing approach, we applied the CASN phosphor silicone in red color (also known as CaAlSiN3:Eu2+) to the said PiG. As a result, with a current of 350 mA, the WLEDs made of PiG-RPL exhibit highly remarkable chromatic performance for the CRI (also known as color rendering index) values determined as Ra = 95.6 with R9 = 95.2 and fidelity/gamut values determined as Rf = 92 with Rg = 99.2. The color quality of the PiG-RPL based WLEDs is steady over a wide range of currents, from 100 to 1000 mA. Moreover, PiG-RPL based WLEDs have better color uniformity than typical PiG based WLEDs. The PiG-RPL structure was proposed in this paper to improve the WLEDs’ chromatic generation as well as chromatic homogeneity. We made the PiGRPL via placing a lens of CASN phosphor above a PiG in green color made of YAGG phosphor. For WLEDs, the PiG-RPL provides extremely remarkable chromatic generation. Furthermore, the WLEDs that are made of PiG-RPL have better color uniformity than those made of PiG and PiG-RPP. The PiG-RPL color converters are considered to be promising for high-power WLEDs, offering great color rendering and color uniformity.